1996
DOI: 10.1073/pnas.93.4.1480
|View full text |Cite
|
Sign up to set email alerts
|

cGMP mediates the vascular and platelet actions of nitric oxide: confirmation using an inhibitor of the soluble guanylyl cyclase.

Abstract: The L-arginine:nitric oxide (NO) pathway is believed to exert many of its physiological effects via stimulation of the soluble guanylyl cyclase (SGC); however, the lack of a selective inhibitor of this enzyme has prevented conclusive demonstration of this mechanism of action. We have found that the compound LH- [1,2,4]oxadiazolo [4,3,-a]quinoxalin-1-one (ODQ) inhibits the elevation of cGMP induced by the NO donor S-nitroso-DL-penicillamine in human platelets and rat vascular smooth muscle (ICso = 10-60 nM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
246
3
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(266 citation statements)
references
References 35 publications
15
246
3
2
Order By: Relevance
“…42 ODQ prevented SNAPinduced increases in cGMP in RASMCs (data not shown), as described previously. 42 Treatment of RASMCs with ODQ also significantly impaired SNAP's ability to inhibit PAI-1 expression in Ang II-stimulated RASMCs ( Figure 6, bottom left). To examine the potential role of cGMP-dependent protein kinase (cGPK) in the regulation of PAI-1 expression, cells were treated with KT5823, an inhibitor of cGPK previously shown to interfere with a variety of other actions of natriuretic factors and nitric oxide.…”
Section: Anf and Cnp Primarily Signal Via Natriuretic Peptide Receptomentioning
confidence: 81%
See 2 more Smart Citations
“…42 ODQ prevented SNAPinduced increases in cGMP in RASMCs (data not shown), as described previously. 42 Treatment of RASMCs with ODQ also significantly impaired SNAP's ability to inhibit PAI-1 expression in Ang II-stimulated RASMCs ( Figure 6, bottom left). To examine the potential role of cGMP-dependent protein kinase (cGPK) in the regulation of PAI-1 expression, cells were treated with KT5823, an inhibitor of cGPK previously shown to interfere with a variety of other actions of natriuretic factors and nitric oxide.…”
Section: Anf and Cnp Primarily Signal Via Natriuretic Peptide Receptomentioning
confidence: 81%
“…40,41 Nitric oxide activates a soluble guanylyl cyclase, which is the primary mediator of its actions in VSMCs. 42 Because cGMP is a major second messenger for both natriuretic peptides and nitric oxide, we examined the role of cGMP in the regulation of PAI-1 expression. Intracellular cGMP was directly elevated by treatment of cells with the membrane-permeant cGMP analogue 8-Br-cGMP for 15 minutes followed by stimulation with 100 nmol/L Ang II for an additional 3-hour incubation.…”
Section: Effect Of Snap On Pai-1 Expression In Rasmcsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even in vascular smooth muscle, a significant component of the relaxation response may be cGMP independent. In some vessels and species, the response may even be completely independent of cGMP [5][6][7][8], and it has been shown that animals deficient in a SNO-metabolizing enzyme have low vascular resistance ( [9], JSS unpublished). By analogy, stringent genetic evidence for a role of NO (per se) in blood pressure control has not been provided.…”
Section: Oxidants As Modulators Of Signal Transductionmentioning
confidence: 99%
“…Plasma, nitric oxide, cGMP and platelet function investigate NO-mediated cGMP-independent antiplatelet effects (Tsikas et al, 1999;Homer & Wanstall, 2002); however, a 100 : 1 excess of the NO donor SNAP can result in a partial reversal of ODQ-mediated inhibition of sGC (Moro et al, 1996). In our experiments, a theoretical maximum of 20 mM NO will be released by 10 mM DEA/NO, which is equivalent to the concentration of ODQ used here, and unlikely to be sufficiently high to overcome ODQ-mediated inhibition.…”
Section: Ms Crane Et Almentioning
confidence: 99%